1989
DOI: 10.1007/bf00128864
|View full text |Cite
|
Sign up to set email alerts
|

Hodograph method in non-Newtonian MHD transverse fluid flows

Abstract: Equations for steady plane flows of non-Newtonian electrically conducting fluids of finite and infinite electrical conductivity are recast in the hodograph plane by using the Legendre transform function of the stream-function when the magnetic field is normal to the flow plane. Four examples are worked out to illustrate the developed theory. Solutions and geometries for these examples are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Introducing L(u, v) in the system (16)- (19), with j, w 1 , w 2 , given by (15), (20) respectively, it follows that (16) is identically satisfied and the system may be replaced by…”
Section: Equations In Hodograph Planementioning
confidence: 99%
See 3 more Smart Citations
“…Introducing L(u, v) in the system (16)- (19), with j, w 1 , w 2 , given by (15), (20) respectively, it follows that (16) is identically satisfied and the system may be replaced by…”
Section: Equations In Hodograph Planementioning
confidence: 99%
“…In the studies of non-Newtonian fluids not only the non-linearities increase considerably, in comparison to the non-linearities occurring in the inertia part of the Navier-Stokes equations, but in certain cases the order of differential equation also increase. In case of a homogenous incompressible fluid of second grade, it is found that the governing equations are, in general, of third order, as compared to the second order Navier-Stokes equations [15] [16]. For obtaining exact solutions transformation techniques involving inverse or semi-inverse methods are used for reformulation of equations in solvable form.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ames [4]. In several research papers of varied area such as gas dynamics [23,19], viscous fluids [16], non-Newtonian fluids [51,44], and MHD Newtonian and non-Newtonian fluid flows [65,17] hodograph transformation method has been widely used. A large number of authors [16,14,5,15,59,61,66,2,43,42,56,36,33,53,34,54,58,69] applied this technique to study various MHD and non-MHD fluid flows.…”
Section: Introductionmentioning
confidence: 99%